Non-high-density lipoprotein cholesterol and risk of cardiovascular disease in the general population and patients with type 2 diabetes: A systematic review and meta-analysis. (January 2019) - Cao, Yanchao; Yan, Liqiu; Guo, Nan; Yu, Na; Wang, Yunfei; Cao, Xufen; Yang, Shuping; Lv, Fengfeng
Highlights: Conflicting results have reported on the association of non-HDL-C with CVD risk. The general population with the highest non-HDL-C level increased by 62% CVD risk. Type 2 diabetes patients with the highest non-HDL-C level increased by 99% CVD risk. Higher non-HDL-C level was not associated with cardiovascular death risk in both populations. Optimal cutoff value of non-HDL-C for predicting CVD should be further explored. Abstract: Aims: To examine the relationship of non-high-density lipoprotein cholesterol (non-HDL-C) level with cardiovascular disease (CVD) risk in type 2 diabetes patients and the general population by conducting a meta-analysis. Methods: We made a comprehensive literature search for relevant observational studies investigating the relationship of non-HDL-C level with CVD risk in the general population and type 2 diabetes patients using the PubMed and Embase databases. Pooled risk ratio (RR) with 95% confidence intervals (CI) was calculated for the highest versus the reference lower non-HDL-Cl. Results: A total of 13 studies with 156, 381 individuals were included. The pooled RR of CVD was 1.59 (95% CI 1.46–1.72) in the general population and 1.99 (95% CI 1.57–2.51) in type 2 diabetes patients. Subgroup analysis showed the similar effect of non-HDL-C on CVD risk between men (RR1.98; 95% CI 1.70–2.30) and women (RR 1.63; 95% CI 1.35–1.96). However, elevated non-HDL-C was not associated with higher risk of cardiovascular mortality in the general population (RR 1.64; 95% CI 0.96–2.80) and type 2 diabetes patients (RR 1.08; 95% CI 0.57–2.07). Conclusions: Elevated non-HDL-C level is associated with an increased risk of CVD in the general population and type 2 diabetes patients.